Analisis Pengelolaan Sumber Daya Manusia dan Budaya Organisasi terhadap Efektivitas Proses Bisnis Jasa Influencer - Mikhael Francois Josua; Adi Teguh Suprapto (Business Management Journal, 2022)
Technology use has increased in this era of globalization and has many advantages in all spheres, particularly in businesses. Technology is used by businesses as a marketing tool to advertise their services and draw customers in. However, the organization and management of the company's human resources also have an impact on the process of creating commercials. Using multiple regression research techniques, this study was undertaken to ascertain the impact of organizational culture and human resource management on the efficiency of service business processes. The findings show that influencer marketing for services has a major impact on human resource management and organizational culture simultaneously and to a lesser extent. PT. AdAsia Technology Indonesia.